Revitalisasi Pancasila dalam Pembangunan Hukum Nasional Di Era Globalisasi - Zuhraini (PRANATA HUKUM, 2012)
Growth in society effect of globalization have influenced growth in tatanan punish national. In the end existing law norm have to can adapt to change that happened, but non meaning have to take off embraced values, like life view, Five Principles state s philosophy and ideology which have become the source of from all source of law. For that law remain to have to can alli arising out implication effect of current of globaliasi with elementary value which contained in Five Principles. becoming elementary question is how development of law in Indonesia arising out of globalization values with values in Five Principles payload as source of from all source of existing law. Pursuant to result of Five Principles study intactly have to be seen by as " guidelines national", as " Standard national, principles and norm" what at the same time load " responsibility human and rights human". Five Principles also can function as margin of of appreciation as appreciation margin or boundary to law which live in society which is pluralistic so that can be agreed in life of national law.